Front Cover: Molecular Basis of the Antiangiogenic Action of Rosmarinic Acid, a Natural Compound Targeting Fibroblast Growth Factor‐2/FGFR Interactions (ChemBioChem 1/2021). (16th December 2020) - Pagano, Katiuscia; Carminati, Laura; Tomaselli, Simona; Molinari, Henriette; Taraboletti, Giulia; Ragona, Laura
Abstract : Less complex : Right: Fibroblast growth factor‐2 (FGF2, orange) interacts with the extracellular domain of fibroblast growth factor receptor (FGFR, red/blue) and induces the autophosphorylation of FGFR intracellular tyrosine kinase domain that, in turn, leads to complex signal transduction pathways regulating angiogenesis, tissue homeostasis, wound repair and cancer. Left: Rosmarinic acid (RA), a polyphenol present in Laminaceae family plants, binds to the extracellular domain of FGFR and induces dissociation of the FGF2/FGFR complex. NMR and docking approaches demonstrate that RA directly competes with FGF2 for the same binding site and induces allosteric perturbations further destabilizing the complex. Cellular studies show that RA binding inhibits FGF2‐induced FGFR phosphorylation, a key step in FGFR signalling. More information can be found in the full paper by K. Pagano, L. Ragona et al.